Regime-dependent linkages between securitized real estate market and major financial markets: some international evidence. (2nd September 2018) - Liow, Kim Hiang; Ye, Qing
ABSTRACT: We employ Markov regime-switching approach to explore the regime-dependent linkages between securitized real estate market and stock, money, bond and foreign exchange markets for 10 economies. During high-volatility periods in securitized property markets, stock market return, and to some extent, changes to foreign exchange market rates impose stronger and positive impact on securitized real estate market returns. Moreover, stock and bond market risks are linked negatively to securitized real estate market risk. Although the asymmetrical regime-dependent influences of the financial market performance indicators on the SRE market do vary across the 10 economies studied in terms of direction and significance, the results highlight the risk of increased exposure of securitized property markets to financial markets during high-volatility market conditions which the investors and policymakers should be alerted to.